A Fungal Arrestin Protein Contributes to Cell Cycle Progression and Pathogenesis - Calla L. Telzrow (American Society for Microbiology, 2019)
ABSTRACT Arrestins, a structurally specialized and functionally diverse group of proteins, are central regulators of adaptive cellular responses in eukaryotes. Previous studies on fungal arrestins have demonstrated their capacity to modulate diverse cellular processes through their adaptor functions, facilitating the localization and function of other proteins. However, the mechanisms by which arrestin-regulated processes are involved in fungal virulence remain unexplored. We have identified a small family of four arrestins, Ali1, Ali2, Ali3, and Ali4, in the human fungal pathogen Cryptococcus neoformans. Using complementary microscopy, proteomic, and reverse genetics techniques, we have defined a role for Ali1 as a novel contributor to cytokinesis, a fundamental cell cycle-associated process. We observed that Ali1 strongly interacts with proteins involved in lipid synthesis, and that ali1Δ mutant phenotypes are rescued by supplementation with lipid precursors that are used to build cellular membranes. From these data, we hypothesize that Ali1 contributes to cytokinesis by serving as an adaptor protein, facilitating the localization of enzymes that modify the plasma membrane during cell division, specifically the fatty acid synthases Fas1 and Fas2. Finally, we assessed the contributions of the C. neoformans arrestin family to virulence to better understand the mechanisms by which arrestin-regulated adaptive cellular responses influence fungal infection. We observed that the C. neoformans arrestin family contributes to virulence, and that the individual arrestin proteins likely fulfill distinct functions that are important for disease progression. IMPORTANCE To survive under unpredictable conditions, all organisms must adapt to stressors by regulating adaptive cellular responses. Arrestin proteins are conserved regulators of adaptive cellular responses in eukaryotes. Studies that have been limited to mammals and model fungi have demonstrated that the disruption of arrestin-regulated pathways is detrimental for viability. The human fungal pathogen Cryptococcus neoformans causes more than 180,000 infection-related deaths annually, especially among immunocompromised patients. In addition to being genetically tractable, C. neoformans has a small arrestin family of four members, lending itself to a comprehensive characterization of its arrestin family. This study serves as a functional analysis of arrestins in a pathogen, particularly in the context of fungal fitness and virulence. We investigate the functions of one arrestin protein, Ali1, and define its novel contributions to cytokinesis. We additionally explore the virulence contributions of the C. neoformans arrestin family and find that they contribute to disease establishment and progression.